2015
DOI: 10.1016/j.biomaterials.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized skeletal muscle as an in vitro model for studying drug-extracellular matrix interactions

Abstract: Several factors can affect drug absorption after intramuscular (IM) injection: drug solubility, drug transport across cell membranes, and drug metabolism at the injection site. We found that potential interactions between the drug and the extracellular matrix (ECM) at the injection site can also affect the rate of absorption post-injection. Using decellularized skeletal muscle, we developed a simple method to model drug absorption after IM injection, and showed that the nature of the drug-ECM interaction could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…This finding is consistent with previous studies that created dME based scaffolds for musculoskeletal tissue repair (e.g. bone, muscle, tendon), in which evidence of dME promoting recellularization and organic molecule adsorption had been reported [57][58][59]. We also confirmed that dMEP scaffolds contained a significantly higher initial collagen components than the PCL scaffolds, and that this component was accessible to exogenous proteases.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous studies that created dME based scaffolds for musculoskeletal tissue repair (e.g. bone, muscle, tendon), in which evidence of dME promoting recellularization and organic molecule adsorption had been reported [57][58][59]. We also confirmed that dMEP scaffolds contained a significantly higher initial collagen components than the PCL scaffolds, and that this component was accessible to exogenous proteases.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, it was shown that normalizing tumor ECM environment was able to “revert” cancer cell neoplastic phenotype [ 15 ] and limit tumor growth and dissemination [ 16 ], highlighting the essential role of ECM physicochemical properties on cancer development. These ECM-guided cell biological changes suggest potential therapeutic approaches that target ECM rather than cancer cells for treatment or that treatments can be ineffective if, for example, a dense ECM or binding with the ECM limits drug availability [ 10 , 17 , 18 ]. Therefore, it is important to study cancer cell biology and regulatory mechanisms in tissue-mimicking microenvironments, which are able to facilitate unveiling the nature of carcinogenic processes when it comes to cancer cell adhesion, proliferation, migration, invasion, metastasis, and drug treatment in native tissue space [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because Matrigel is derived from a tumor of the basement membrane, and promotes cell growth, it is particularly beneficial in drug screening and development 108 , 109 , 110 . The production of 3D cell cultures using ECM scaffolds developed through decellularization has been, or is currently being, demonstrated in cardiac, adipose, hepatic, pleural, vascular, skeletal muscle, neuronal, and renal tissues 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 …”
Section: Future Directionsmentioning
confidence: 99%